Two novel aromatic hydrocarbons: facile synthesis, photophysical properties and applications in deep-blue electroluminescence. Issue 28 (28th April 2020) - Gao, Zhixiang; Wu, Yuling; Qu, Wenshan; Li, Tianbao; Yang, Tingting; Fan, Xiaxia; Dong, Lijuan; Shi, Yunlong; Cheng, Xuerui; Ren, Yufen; Tao, Peng
Abstract : Novel solution processable aromatic hydrocarbons have been designed and synthesized for deep-blue OLEDs with a maximum emission peak of 410 nm and CIE coordinates of (0.16, 0.08). Abstract : Two efficient novel fluorescent naphthalene and fluorene-based aromatic hydrocarbon isomers (1 and 2 ) are prepared and investigated for organic electroluminescence. These compounds show bright violet to deep-blue emission, narrow full width at half maximum (52 nm), and high photoluminescence efficiency ( e.g. 0.61 in CH2 Cl2, 0.67 in film). Alternation of substituent position on the naphthalene moiety can give rise to remarkable emission variation. The relatively large torsion angle between naphthalene and fluorene suppresses the π–π interactions by weakening the intermolecular interactions in the solid state, which can result in highly efficient fluorescence. Moreover, the 1931 Commission Internationale de L'Eclairage coordinates and maximum emission peak for deep-blue electroluminescence based on 1 are (0.16, 0.08) and 410 nm, respectively.